Design of Hand Rehabilitation Training Device based on SMA - Feng Kaidi; Yang Yan (Jixie chuandong)
A new type of hand rehabilitation training device based on shape memory alloy spring is proposed for the existing hand rehabilitation training device with complex structure and poor portability. The device realizes miniaturization， portability and easy operation of hand rehabilitation training device through underactuation mode， driven by single memory alloy spring and multiple common springs. The relationship between the output force and the output stroke of the shape memory alloy spring is investigated and experimentally verified. The influencing factors of knuckle output force are analyzed. By comparing PID control and fuzzy control， the control efficiency of the device is improved. The simulation and experiment on the device verify the rationality of the device， and provide a research basis for the optimization of the device in the next step.